Veritas observations of the unusual extragalactic transient swift J164449.3+573451 - Aliu, E. (2011)
We report on very high energy (E > 100 GeV) gamma-ray observations of Swift J164449.3+573451, an unusual transient object first detected by the Swift Observatory and later detected by multiple radio, optical, and X-ray observatories.A total exposure of 28 hr was obtained on Swift J164449.3+573451 with the Very Energetic Radiation Imaging Telescope Array System (VERITAS) during 2011 March 28-April 15. We do not detect the source and place a differential upper limit on the emission at 500 GeV during these observations of 1.4 x 10^-12 erg cm^-2 s^-1 (99 % confidence level). We also present time-resolved upper limits and use a flux limit averaged over the X-ray flaring period to constrain various emission scenarios that can accommodate both the radio-through-X-ray emission detected from the source and the lack of detection by VERITAS.